From Eastern inspiration to unisex fashion: a case study on traditional Chinese Shenyi attire - Kuo, Yu Pei; Vongphantuset, Jirawat; Joneurairatana, Eakachat (Humanities, Arts and Social Sciences Studies, 2021)
Unisex fashion is not simply a trend but the new normal under the veneer of people preferring to express self-identity through their garments. However, following the modern standard fashion design process and techniques, prototype or draping, designers define the gender selected in advance, which presents a problem between the traditional design method and the new concept. This study aims to provide a solution and inspire references for the design of unisex fashion. Studies mainly use the past hundred years of Western culture as a basis for unisex fashion. However, people should understand unisex fashion in a global cultural context. This study conducts a review of the history of ancient attire, in particular, unisex clothing in the western and eastern regions. We present different concepts and methods in Western culture, such as the ancient Greeks’ Chiton and ancient Romans’ Tunic. However, Eastern traditional attire has referred to the unisex concept by other methods, such as Shenyi in China and Jongkraben from Thailand. We take Shenyi as a case study because of its classic 2D technique and influence in Asia. This timeless unisex attire taken from history, modernization, garment structure, and wearable skills enforces the analysis of unisex fashion. However, we not only explore Shenyi but also compare it with other ancient clothing. Through this study, we expect to inspire the development of a new paradigm in the design of unisex fashion.